5th IET International Conference on Power Electronics, Machines and Drives (PEMD 2010) 2010
DOI: 10.1049/cp.2010.0094
|View full text |Cite
|
Sign up to set email alerts
|

Grid integration of offshore wind farms using multi-terminal DC transmission systems (MTDC)

Abstract: This paper discusses the control flexibility and fault ridethrough capability of the bi-polar multi-terminal DC transmission system based on voltage source converters used for integration of large-scale offshore wind farms. Issues such as voltage support and short-term frequency stabilization of the AC network utilizing the stored energy in the wind turbine inertia and DC link capacitors are discussed. Regarding control flexibility, two aspects are presented: power sharing between the grid-side converters by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Up to now, DC technology applied in the transmission network has been exploited a lot by many researchers around the world [1]- [3]. Multi-terminal direct current (MTDC) transmission systems based on voltage source converters (VSC) have been commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, DC technology applied in the transmission network has been exploited a lot by many researchers around the world [1]- [3]. Multi-terminal direct current (MTDC) transmission systems based on voltage source converters (VSC) have been commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, flexible DC technology applied in the transmission network has been exploited a lot throughout the world both theoretically and practically [1]- [3]. Control strategies for MTDC networks are introduced in [4]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…By far, many literatures have discussed the advantages of using voltage source converter (VSC) for MTDC application and concluded that VSC MTDC can provide significant benefit for transmission network, such as the decoupled control of active power and reactive power, the support to weak AC system, the black start capability and small footprint [7][8] [9], etc. However, nowadays the maximum capacity of a VSC HVDC line is still limited within 2,000 MW level whereas the line commutated converter (LCC) based MTDC takes advantages of low cost and large capacity of more than 7,000 MW per bipole.…”
Section: Introductionmentioning
confidence: 99%
“…The basic control method "current margin control" for parallel MTDC, was discussed in 1963 [7]. The early development of parallel MTDC technology is summarized by [10], in which the papers published in 17 years (1963-1980) had been reviewed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation